Expert .NET Delivery Using NAnt and CruiseControl.NET - Holmes, Josh (Apress : Imprint: Apress, 2005)
At first glance, building and deploying applications seem simple enough. But in fact, difficult releases without any confidence or processes backing them are very common. Integration and management of a new deployment can be laborious and fraught with risk. So as team size and volume of projects grow, management becomes more difficult and risk more pronounced. This book is a guide to the implementation of good processes in a .NET environment. Author Marc Holmes focuses on actual implementation, and details patterns and anti-patterns to watch out for. He also provides a practical and in-depth look at NAnt and CruiseControl.NET, and solutions to common problem scenarios. For additional insights, visit the author's blog, Marc: My Words.